Ultrasound-Diagnosed Non-Alcoholic Fatty Liver Disease among Medical Check Up Patients - Suharjo B Cahyono; Putut Bayupurnama; Neneng Ratnasari; Sutanto Maduseno; Siti Nurdjanah (The Indonesian Society for Digestive Endoscopy, 2013)
Background: Non-alcoholic fatty liver disease (NAFLD) is recognised as one of the most important causes of chronic liver disease and has become an important health issue in many countries. The aim of the study wasto evaluate the prevalence and risk factors of NAFLD patients based on ultrasound diagnosed in medical check up setting.Method: In this study, of 2,105 patients undergoing medical check up in Charitas Hospital, Palembang between January 2011 to August 2013, 115 NAFLD patients and 113 non-NAFLD patients as controls were included. Diagnosis of NAFLD was based on ultrasound appearance, patients did not consume alcohol, with negative HBsAg and hepatitis C virus antibodies.Results: The prevalence of NAFLD in medical check up patients was 7.9% whereas 39% patients had normal body mass index (BMI) ( 25 kg/m2). Patients with NAFLD compared with non-NAFLD patients had higher values of BMI (p 0.001), triglycerides (p = 0.001), aspartate aminostransferase (AST) (p 0.001), alanine aminotransferase (ALT) (p 0.001), fasting glucose (p = 0.002), and lower HDL cholesterol (p = 0.001). Obesity was the strongest associated factor for NAFLD (95% CI = 1.87-7.85; OR = 3.83; p 0.001), followed by high glucose levels (95% CI = 1.38 - 8.31; OR = 3.83; p = 0.008) and hypertriglyceridemia (95% CI = 1.38 - 4.11;OR = 2.38; p = 0.002).Conclusion: About 7.9% patients suffered from NAFLD. Approximately 39% medical check up patients had NAFLD with normal BMI. Obesity, hypertriglyceridemia and high glucose levels were the risk factors for NAFLD.Keywords: non-alcoholic liver disease, body mass index, prevalence, metabolic syndrome